2001
DOI: 10.1136/ard.60.12.1097
|View full text |Cite
|
Sign up to set email alerts
|

Detection of immune deposits in skin lesions of patients with Wegener's granulomatosis

Abstract: Background-Wegener's granulomatosis (WG) is considered a pauci-immune systemic vasculitis based on the absence of immune deposits in renal biopsies of patients with active disease. In animal models of antineutrophil cytoplasmic antibody (ANCA) associated glomerulonephritis, immune deposits along the glomerular capillary wall are present at early stages of lesion development. These deposits are degraded rapidly, resulting in "pauci-immune" lesions. Objective-To test the hypothesis that immune deposits can also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…It was demonstrated in animal models that cellular immunity may interfere with the formation of the immune complex [28]. Other animal experiments and some clinical findings also suggest that AAV with immune-complex deposits may represent an early stage in the disease course [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated in animal models that cellular immunity may interfere with the formation of the immune complex [28]. Other animal experiments and some clinical findings also suggest that AAV with immune-complex deposits may represent an early stage in the disease course [29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…The skin may be an exception to the rule since one study reported cutaneous vascular immune complex deposits. The authors considered these lesions "early" in contrast to the "late" pauci-immune lesions [25].…”
Section: Vasculitismentioning
confidence: 99%
“…Patients presenting with LCV are more likely to have concurrent musculoskeletal and renal involvement and a more rapidly progressive disease course when compared to patients without cutaneous manifestations and are more likely to, over time, develop renal, musculoskeletal, and ocular manifestations when compared to patients with granulomatous dermatitis (Barksdale et al, 1995). While direct immunofluorescence typically fails to demonstrate immunoglobulin or complement deposition on renal biopsies, skin biopsies frequently show perivascular deposits of IgG, IgM, IgA, and C3 in subepidermal and dermal vessels (Brons et al, 2001). In patients who have had a relapse of WG, immunoglobulin deposits can be seen along the basement membrane and within the dermis (Brons et al, 2001).…”
Section: Wegener's Granulomatosismentioning
confidence: 99%
“…While direct immunofluorescence typically fails to demonstrate immunoglobulin or complement deposition on renal biopsies, skin biopsies frequently show perivascular deposits of IgG, IgM, IgA, and C3 in subepidermal and dermal vessels (Brons et al, 2001). In patients who have had a relapse of WG, immunoglobulin deposits can be seen along the basement membrane and within the dermis (Brons et al, 2001). …”
Section: Wegener's Granulomatosismentioning
confidence: 99%